Assessment of trace elements contamination and human health risk based on Monte Carlo simulation in a karst groundwater system affected by industrial activities - Liyun Yang; Qixin Wu; Shilin Gao; Meixue Peng; Jianping Zhu; Jie Zeng; Li Shi; Xinghe Li (Ecotoxicology and Environmental Safety)
Groundwater in karst regions is a vital drinking water source, but it is highly susceptible to contamination from industrial activities, which exacerbate pollution and pose health risks. This study investigated the concentration, spatial distribution, quality, health risks and sources of trace elements (TEs) in groundwater within a newly established industrial park in Guiyang, a representative city with a karst landscape. The results indicated that the trace element concentrations followed the order: Ti > Fe > Al > Ni > Cr > Mn > V > Cu > As > Co. Correlation Analysis (CA) and Hierarchical Cluster Analysis (HCA) suggested that the sources of TEs are multifaceted, with industrial activities identified as the primary influencing factor. Monte Carlo simulations revealed that the non-carcinogenic risk (NCR) associated with each element was negligible. However, due to industrial activities, Cr, Ni and As exhibited significant carcinogenic risks. As one of the characteristic pollutants of the electroplating industry, Cr presented the highest potential risk. The total carcinogenic risks (TCR) for adults and children were 3.24E-05 and 3.78E-05, respectively, both exceeding the acceptable risk threshold of 1E-06. These results make a meaningful contribution to the management of vulnerable aquifers in karst industrial areas, with an emphasis on protection against TEs contamination, which is critical for ensuring groundwater safeguard and protecting public health.